A design framework for adaptive digital twins. Issue 1 (2020) - Erkoyuncu, John Ahmet; del Amo, Iñigo Fernández; Ariansyah, Dedy; Bulka, Dominik; Vrabič, Rok; Roy, Rajkumar
Abstract: Digital Twin (DT) is a 'living' entity that offers potential with monitoring and improving functionality of interconnected complex engineering systems (CESs). However, lack of approaches for adaptively connecting the existing brownfield systems and their data limits the use of DTs. This paper develops a new DT design framework that uses ontologies to enable co-evolution with the CES by capturing data in terms of variety, velocity, and volume across the asset life-cycle. The framework has been tested successfully on a helicopter gearbox demonstrator and a mobile robotic system across their life cycles, illustrating DT adaptiveness without the data architecture needing to be modified.